2014
DOI: 10.5152/akd.2014.4968
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic characteristics of left atrium and openings of pulmonary veins

Abstract: Objective: Left atrium (LA) and left atrial pulmonary venous anatomy have clinical importance for atrial fibrillation (AF) and cardiac tumor surgery. A detailed anatomic knowledge of these structures may faciliate clinical evaluations. The aim of this study was to assess LA size and to demonstrate other anatomic features of LA with pulmonary vein openings in normal population. Methods: This descriptive laboratory study was performed in 56 hearts of adult formalin fixed cadavers. The number of pulmonary vein op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The typical anatomy of right and left PV are two separate ostia on each side, this was true in our series in more than 66% on the right and almost 82% on the left, comparing to literature data where the typical anatomy of right PV was observed in 60–88% and of left PV in 41–91% [ 1 , 23 , 28 , 32 ]. A common trunk was more frequent on the left (17.8%) than on the right (4%), which is similar to most of the literature data: 6–33% [ 1 , 17 , 18 , 23 , 28 ] and 0.76–4%, respectively [ 3 , 5 , 17 , 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…The typical anatomy of right and left PV are two separate ostia on each side, this was true in our series in more than 66% on the right and almost 82% on the left, comparing to literature data where the typical anatomy of right PV was observed in 60–88% and of left PV in 41–91% [ 1 , 23 , 28 , 32 ]. A common trunk was more frequent on the left (17.8%) than on the right (4%), which is similar to most of the literature data: 6–33% [ 1 , 17 , 18 , 23 , 28 ] and 0.76–4%, respectively [ 3 , 5 , 17 , 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…Also, McLellan et al noticed the classical pattern and the left common PV ostium in 47% and 37% of AF patients respectively; they also concluded that the presence of the left common PV was associated with an increased freedom from AF after catheter ablation (assessed by using Cox regression analysis in univariate and multivariate models) ( McLellan et al, 2014 ). In conclusion, we can note a trend that the common left PV ostia are more frequently found in AF patients, while in the normal population they are the minor variation (up to 15%) ( Aktan Ikiz, Üçerler & Özgür, 2014 ; Woźniak-Skowerska et al, 2011 ). Isolation of such small ostia entails much higher risk of PV stenosis caused by catheter ablation.…”
Section: Discussionmentioning
confidence: 62%
“…There is no doubt that the clinical importance of pulmonary vein anatomy is crucial for planning and performing the catheter and balloon-based pulmonary vein ablation (isolation) procedures ( Aktan Ikiz, Üçerler & Özgür, 2014 ; Köse et al, 2012 ; Mayor, 2015 ; Nalliah et al, 2015 ; Rettmann et al, 2015 ; Sarabanda et al, 2005 ; Stanford & Breen, 2005 ). Classical 4 PV ostia pattern could be observed in 68–81% of all individuals ( Aktan Ikiz, Üçerler & Özgür, 2014 ; Kaseno et al, 2008 ; L C et al, 2014 ; Marom et al, 2004 ; Scharf et al, 2003 ; Tekbas et al, 2012 ). The present study confirms that a common PV ostium occurring on the left side is the most frequent anatomical variation in the healthy population, whereas an additional ostium is most common on the right side of the left atrium ( Prasanna et al, 2014 ; Stanford & Breen, 2005 ; Vasamreddy et al, 2004 ; Woźniak-Skowerska et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the anatomical variations of PV ostia were examined in 73 studies including 13,811 subjects (Abadir et al, 2019; Akkaya et al, 2018; Aktan Ikiz et al, 2014; Allgayer et al, 2008; Altinkaynak & Koktener, 2019; Angulo Hervias et al, 2020; Anselme et al, 2006; Anselmino et al, 2011; Artuso et al, 2005; Baszko et al, 2012; Benini et al, 2008; Beukema et al, 2010; Bittner et al, 2011; Boersma et al, 2008; Bogot et al, 2009; Bourier et al, 2013; Brunelli et al, 2012; Carreras et al, 2005; Chen et al, 2017; Cirillo et al, 2004; Cronin et al, 2007; Dong et al, 2005, 2006; Fodi et al, 2013; Hamdan et al, 2009; Harbi et al, 2014; Hauser et al, 2006, 2015; Hof et al, 2009; Hoffmeister et al, 2007; Huang et al, 2018; Hunter et al, 2010; Ihara et al, 2011; Imanli et al, 2017; Istratoaie et al, 2019; Jongbloed et al, 2004; Jongbloed, Bax, et al, 2005; Jongbloed, Dirksen, et al, 2005; Kanaji et al, 2016; Kaseno et al, 2008; Klimek‐Piotrowska et al, 2016; Knecht et al, 2013; Koçyiğit et al, 2017; Krum et al, 2013; Kubala et al, 2011; Lickfett et al, 2004, 2005; Mansour et al, 2004; Martinez Urabayen et al, 2021; Merchant et al, 2016; Metzner et al, 2012; Micochova et al, 2005; Mulder et al, 2011; Niculescu et al, 2006; Patel et al, 2013; Pontone et al, 2015; Prasanna et a...…”
Section: Resultsmentioning
confidence: 99%